Model of Emergency and Observation Nursing Services at the Community Health Center in East Java - Dwi Ananto Wibrata; Siti Nurkholifah; Adin Mu’afiro (Humanistic Network for Science and Technology (HNST), 2017)
Public health centers as the spearhead of health services, also provide 'emergency and observation' nursing services, due to the high number of accidents in East Java. The purpose of this study was to develop the nurse's performance model in providing 'emergency and obeservation' nursing services at Puskesgadarsi ('Emergency and Observation' Community Health Center) in East Java, using cross sectional design. The subjects of 120 nurses were selected by multi stage sampling technique. Data were collected through questionnaires and FGDs, and then analyzed using structural equation modeling to produce an model of ‘emergency and observation’ nursing service for nurses at Puskesgadarsi. Components of the model were reinforcing factors, personal factors, cognition factors, affection factors, commitment, interpersonal, reinforcement and nurse performance. Nurses can use this model in providing nursing services with due regard to their knowledge and skills, facilities and infrastructure, as well as interaction and self-reinforcement, so as to be able to perform nursing services 'emergency and observation' well. Keywords: Nursing service, Emergency and observation, Community health center